2019
DOI: 10.12928/telkomnika.v17i2.10149
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of 940 nm and 1450 nm near infrared sensor for glucose concentration monitoring

Abstract: In order to manage their blood glucose level, diabetics have to test their blood glucose level regularly. Unfortunately, the current blood glucose measurement device is uncomfortable, painful, event costly for the diabetics; therefore, a lot of effort is given to develop a noninvasive blood glucose meter. We studied the potential of two near infrared wavelength i.e. 1450 and 940 nm as glucose sensor. Each sensor consists of a light emitting diode (LED) as light source, a photodiode that is sensitive to that wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…These sensor DC output voltages from the three rooms were lower almost half of the output voltages from air media. This result was consistent with our previous result [25]. Water absorbed NIR light and caused noises [26].…”
Section: Results and Analysissupporting
confidence: 94%
See 1 more Smart Citation
“…These sensor DC output voltages from the three rooms were lower almost half of the output voltages from air media. This result was consistent with our previous result [25]. Water absorbed NIR light and caused noises [26].…”
Section: Results and Analysissupporting
confidence: 94%
“…After passing through the filter the effective output voltages from the sensor were reduced to zero. The effective output voltages were a bit higher than the effective voltages with water media for room A and B; it meant that noises with glucose solution were higher than with water media [25]. The sensor average output voltage for the three rooms with glucose solution media was 2.3368 V. There was voltage difference between sensor average output voltage with water and glucose solution media from the three rooms and it could be concluded that the sensor had the potential as a blood glucose level meter.…”
Section: Results and Analysismentioning
confidence: 90%
“…Figure 10 shows a regression analysis example of a subject which indicates that voltage PPG reading increases with the increase of real BGC. The regression coefficients were calculated from (8) and (9) and were substituted in (7) for the prediction of non-invasive glucose concentration. When the system was fully calibrated, the validation data sets for each subject were used to test the performance of the measurement model.…”
Section: Resultsmentioning
confidence: 99%
“…The concept is to irradiate a particular wavelength range of optical radiation on the avascular region of the body and obtain the transmission Photoplethysmography signal (PPG). Near-infrared (NIR) spectroscopy which uses light in (750-2500 nm) wavelength range is one of the most widely recommended optical technique because of its high penetration in skins, very simple and affordable equipment as compared to other optical methods [7][8][9] different bands in these regions are combination overtone band (2000-2500 nm), first overtone band (1400-2050 nm) and second overtone absorption bands (750-1550 nm) [10]. The absorbance of the glucose bonds (C-H, O-H) is strong in combination and first overtone regions but there are some disadvantages in these regions due to three causes.…”
Section: Introductionmentioning
confidence: 99%
“…A plethora of highly intrusive portable blood sugar test kits have arrived on the market; these kits take blood samples from capillaries, which are still painful and uncomfortable and may potentially pose a risk for infection (Abidin et al, 2015). Even with disposable strips, they remain expensive (Bruen et al, 2017;Prawiroredjo & Julian, 2019). Thus, the development of a non-invasive blood sugar meter-a convenient and painless device for monitoring blood sugar levels-is imperative.…”
Section: Introductionmentioning
confidence: 99%